2012
DOI: 10.1109/tbme.2012.2217495
|View full text |Cite
|
Sign up to set email alerts
|

Toward an EEG-Based Recognition of Music Liking Using Time-Frequency Analysis

Abstract: Affective phenomena, as reflected through brain activity, could constitute an effective index for the detection of music preference. In this vein, this paper focuses on the discrimination between subjects' electroencephalogram (EEG) responses to self-assessed liked or disliked music, acquired during an experimental procedure, by evaluating different feature extraction approaches and classifiers to this end. Feature extraction is based on time-frequency (TF) analysis by implementing three TF techniques, i.e., s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
129
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(141 citation statements)
references
References 36 publications
11
129
0
1
Order By: Relevance
“…It decomposes the signal into Intrinsic Mode Functions (IMF) along with a trend, and obtains instantaneous frequency data. Hadjidimitriou et al extracted HHS-based energy as the EEG features to study the music liking of the subjects [32]. They found that time-frequency features were more resistant to noise than the STFT-based features, which only extracted frequency features.…”
Section: Author and Study Year Eeg Features Extraction Methods Dimensionmentioning
confidence: 99%
“…It decomposes the signal into Intrinsic Mode Functions (IMF) along with a trend, and obtains instantaneous frequency data. Hadjidimitriou et al extracted HHS-based energy as the EEG features to study the music liking of the subjects [32]. They found that time-frequency features were more resistant to noise than the STFT-based features, which only extracted frequency features.…”
Section: Author and Study Year Eeg Features Extraction Methods Dimensionmentioning
confidence: 99%
“…In these studies, brain signals were recorded using an EEG headset while the subject listens to music [44,53,58,100,110,112,115,116,151,154,190,205,216,220,222,235,276,279]. Moreover, the subjects' emotions were recognized as displayed by EEG signals.…”
Section: Domain Description Referencesmentioning
confidence: 99%
“…EEG recordings were conducted using the Emotive EPOC 14 channel EEG wireless recording headset (Emotive Systems, Inc., San Francisco, CA) (Hadjidimitriou and Hadjileontiadis, 2012). The electrode scheme was arranged according to the international 10-20 system and included active electrodes at AF3, F7, F3, FC5, T7, P7, O1, O2, P8, T8, FC6, F4, F8, and AF4 positions, referenced to the common mode sense (CMS-left mastoid)/driven right leg (DRL-right mastoid) ground as shown in Figure 1 (d).…”
Section: Eeg Recordingsmentioning
confidence: 99%